Perancangan Pengalaman Pengguna Aplikasi Website Learning Management System (LMS) dengan Metode Goal-Directed Design (Studi Kasus: Dojobox Bootcamp Academy) - Jonathan Frelispradana Musila; Agi Putra Kharisma; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Dojobox Bootcamp Academy is one of the intensive training for the Software Quality Assurance (SQA) which has been running for one batch. From the classes that were already running, several problems were found, including the difficulty of adjusting the time between participants and the class, unstable internet connection, and difficulties in adjusting the learning tempo. Therefore, learning media that can be accessed more flexibly so that participants can access learning content anywhere and anytime. This is in line with the stakeholder's desire to create a learning management system (LMS) as a material for branding the Dojobox Bootcamp Academy. In this study, Goal-Directed Design is used as an approach to link the needs, desires of users and organizational goals. The end result of this is an interactive prototype with a high-fidelity design. The design was evaluated using qualitative and quantitative tests. Qualitative testing was done by using user testing and getting 30 feedback on interaction and interface improvements. Qualitative testing was carried out using a user experience questionnaire (UEQ) and resulted in the following averages: attractiveness scale with 1.32 (above average), perspicuity scale with 2.02 (excellent), efficiency scale with 1.86 (good), dependability scale with 1.52 (good), stimulation scale with 1.54 (good), and novelty scale with 1.25 (good).